Educação musical e ação cultural na escola - Araújo, Caio Higor Morais (2018)
This work presents the results of a research carried out in the scope of basic education based on the development of a cultural action, with the purpose of proposing the re - signification of the school institution as a cultural space in society. In this sense, I present theoretical reflections on the multiple meanings of this approach together with practical collaborations carried out by members of the school community (students, teachers and managers). I use as bibliographical references studies on contemporary music education, such as OLIVEIRA (2006, 2015, 2016), SWANWICK (2003, 2013) and QUEIROZ (2004, 2010, 2012, 2013, 2014), among others. Regarding human education, I present relevant concepts, values and discussions on the theme of paradigm change in the scientific / academic environment and its repercussion on basic education. For this, I turn to the intellectual production of authors such as MORIN (2011), SANTOS (2001, 2003, 2009), CAPRA (1993, 1995). As a methodology the participant research was used, analyzing the impact of the cultural action called Potiguar Music in the School (3rd edition) held at the Ivonete Maciel Municipal School of elementary school I, in the city of Natal / RN. Two musical educators, 14 teacher educators, 6 teachers of specific disciplines, coordinators and directors participated in this study, who helped to intermediate the process. In this context, I used as research techniques, participant observation, individual and group interviews, audiovisual records, field diary, bibliographic and documentary research. The results indicated that 11 different songs of the local musician were performed, without considering the songs that were only appreciated or used as ambient music. On average, each group developed activities with at least two songs. The main contents were also identified: musical and audiovisual appreciation; corner; literacy through reading, reading and writing; study of the biography of the local artist honored; musical design; tangible and intangible assets of the city of Natal; ecology and environment; dance, theater and body language; crafts; and sign language for the deaf (LIBRAS). I conclude by defending a conception of school as an active cultural space in society, where it is possible to re-signify the institution and the teaching practice with new connections between the curricular contents and the participation of the school community in cultural actions and transdisciplinary pedagogical projects. Cultural action should make the school a place conducive to dialogue and the exercise of the production, creation and circulation of cultures, reducing unequal access to symbolic goods in society.